PENERAPAN HUKUM TERHADAP TINDAK PIDANA ILLEGAL FISHING (STUDI KASUS PENGGUNAAN ALAT TANGKAP MINI TRAWL DI WILAYAH PERAIRAN DESA KUALA PATAH PARANG KECAMATAN SUNGAI BATANG KABUPATEN INDRAGIRI HILIR) - Zulfa Nada Habibie; Davit Rahmadan; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Illegal fishing means any form of fishing activity that violates the law. The use oftrawl nets is categorized as illegal fishing. Law enforcement against illegal fishing in itsregulation is often juxtaposed with other fisheries crimes, namely illegal, unreported andunregulated. The use of mini trawls is often found in the waters of Kuala Patah ParangVillage. Fishing by using trawls can damage and endanger the preservation of theenvironment and marine ecosystems or marine resources because fishing is carried outwithout paying attention to environmental aspects. The purposes of writing this thesis are:First, to determine the legal urgency of the prohibition of the use of mini trawl fishing gear infishing in the waters of Kuala Patah Parang Village, Sungai Batang District, Indragiri HilirRegency, Second, to find out the obstacles and efforts in law enforcement against illegalcriminal acts. fishing using mini trawler fishing gear in the waters of Kuala Patah ParangVillage, Sungai Batang District, Indragiri Hilir Regency.This type of research can be classified in the type of sociological juridical researchwith an approach to field research techniques, interviews, and literature studies. Thisresearch was conducted in Kuala Patah Parang Village, Sungai Batang District, IndragiriHilir Regency. To obtain the desired final result, the data obtained, both primary data andsecondary data, were then analyzed using a qualitative approach which was then described.From the results of this study it can be concluded. First, the urgency of the lawprohibiting the use of mini trawl fishing gear in catching fish in the waters of Kuala PatahParang Village, Sungai Batang District, Indragiri Hilir Regency, namely the increasingnumber of cases of using mini trawl fishing gear and the decreasing number of fish obtainedby traditional fishermen in Kuala Patah Parang Village. . Second, the obstacles faced in lawenforcement against the crime of illegal fishing in the use of mini trawler fishing gear in thewaters of the Kuala Broken Parang Village, namely the lack of personnel, fishermen's humanresources are still relatively low, completeness of facilities and supporting facilities are stilllimited in increasing routine patrols in carry out the task of supervising, protecting andprotecting the community, especially fishermen in the waters, and the low sanctions given.Keywords: Law Enforcement, Illegal Fishing, Mini Trawl.